Peran Sistem Merit dalam Reformasi Birokrasi di Indonesia: Tantangan dan Solusi dalam Perspektif Hukum Administrasi Negara: Peran Sistem Merit dalam Reformasi Birokrasi di Indonesia: Tantangan dan Solusi dalam Perspektif Hukum Administrasi Negara - Aswin Maysura, Neha (Mendapo: Journal of Administrative Law, 2025)
Bureaucratic reform is an important priority in efforts to improve good governance in Indonesia. The merit system, which focuses on individual qualifications, competencies and performance, offers a strategic approach to improving the professionalism, accountability and effectiveness of the state civil apparatus (ASN). However, the implementation of this system faces various challenges, including political intervention, nepotism, and low understanding of meritocracy. Through a state administrative law approach, this research analyzes the role of the merit system in bureaucratic reform, explores implementation challenges, and proposes strategic solutions. This research uses a literature review method by integrating various sources of law, government policies, and previous research. The results show that strengthening regulations, technology-based supervision, and socialization of meritocratic principles are important steps to overcome existing obstacles. Thus, consistent implementation of the merit system is expected to create a bureaucracy that is more transparent, professional, and responsive to the needs of the community.